PERAN HOPE WORLDWIDE INDONESIA DALAM PROGRAM TERAMPIL DIGITAL DI INDONESIA - Maryasih, Niluh Kerti; Surya, Elena Libratia (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This research aims to explain the role of HOPE Worldwide Indonesia in increasing digital literacy in Indonesia. Case study of the HOPE Worldwide Indonesia organization, which is one of the Non-Governmental Organizations (NGO) operating in Indonesia, and the Digital Skills program activities in the Tangerang and Serang area. This research uses role concept theory, the Non-Governmental Organization (NGO) concept, and the Industry 4.0 and Society 5.0 concepts. The method used in this research is a qualitative descriptive method, with the data collection process obtained through literature study from various sources. The results of this research explain that HOPE Worldwide Indonesia as a non-governmental organization working in the social sector plays an important and active role in helping to empower the wider community, especially in the digital era which continues to develop rapidly. From the results of this research, it can be concluded that the Digital Skills program by HOPE Worldwide Indonesia plays a role in providing education, training and counseling related to digital literacy.